Health Information System Development Strategy at Gimpu Community Health Center, Sigi District - Ramadhan, Fanky Fazdianki; Syaodih, Erliany; Agung, Ignatius Wiseto Prasetyo (ProBisnis : Jurnal Manajemen, 2025)
The strategy for developing a health information system at the Gimpu Health Center, Sigi Regency aims to improve efficiency in managing patient service information, which has so far been done conventionally. The recording process that has not been computerized often causes duplication of information and takes a long time to process information. In addition, the manual recording system also has risks to information security, because it is prone to loss or damage. The information system designed in this study is in the form of a software application equipped with an information base (database), which functions as a center for storing information and a tool for entering, processing, and accelerating the preparation of reports. The forms available in the system are designed according to user needs to make them easier to use. Not only does it increase ease of operation, this system is also designed with a high level of security to ensure the accuracy and protection of patient information. The design of this system was developed by implementing the stages in the System Development Life Cycle (SDLC). The implementation of this information system is expected to be a solution to various obstacles faced by the Gimpu Health Center, Sigi Regency in the service process, especially related to recording and managing patient information. The information recorded in the system includes patient visit information, such as date of visit, patient identity (name, place and date of birth, name of head of family), gender, level of education, occupation, domicile area (district/city, sub-district, address/hamlet), and payment method for health services.